A life of Jung - Ronald Hayman (Bloomsbury, 2002)
This biography explores the complex character of one of the world's most influential psychoanalysts. Having gained access to a substantial amount of previously unpublished material, Ronald Hayman offers a rare insight into how Jung's revolutionary ideas grew out of his own extraordinary experiences. With notable objectivity, Hayman investigates the most crucial questions surrounding this enigmatic figure. What actually went on during Jung's sessions with patients? Was his mother insane? Was he a borderline case? What were the consequences of a homosexual episode in his boyhood? Was he pro-Nazi or anti-Semitic? Why did he fail to sustain any of his friendships with men? Did he sometimes mean "God" when he said the "Unconscious"? Why was he so secretive?